Laser metal deposition materials-process-performance characterization studies - Tan, Eddie Zhi'En (Nanyang Technological University, 2021)
This research addresses the development of aspects regarding materials-process-performance characterization of laser metal deposition process as well as the development of a novel joining method using AM techniques. This work presents an establishment of a systematic materials-process-performance framework in characterising LMD in the form of a series of studies. A study of the porosity, defect, and microstructure of LMD built Stainless Steel AISI 316L specimens (SS316L) was performed. Defects were measured and analysed using optical microscopy techniques. Types of defects were identified using metrological quantities of circularity and roundness. The microstructure of the LMD parts were also analysed using SEM/EDX. Calculations were made based on the EDX mapped elemental compositions using Schaeffler diagram in order to identify the solidification mode based on the quantity of δ-ferrite present in the specimen. This study provides insight into the fundamentals of solidification characteristics and the effects of process parameters on defect formations. This study was published in the Additive Manufacturing journal: Tan, E. Z. E., Pang, J. H. L., Kaminski, J., & Pepin, H. (2019). Characterisation of porosity, density, and microstructure of directed energy deposited stainless steel AISI 316L. Additive Manufacturing, 25, 286-296, A detailed study was done to investigate the effects of build strategy on LMD Stainless Steel 316L specimens and provide a framework for characterizing the anisotropic properties and behaviour arising from build strategy pattern effects. A series of tensile tests were used to characterise the mechanical anisotropy of LMD specimens that were produced using long unidirectional, bidirectional, and short unidirectional raster scan build strategies. Differences in the thermal history between the three build strategy raster scan patterns resulted in differences in tensile mechanical properties, microstructural grain sizes, fracture surface topology, and hardness properties. This indicates that there is an anisotropic property that arises from different build strategies used in AM-built specimens. This study was accepted as a publication in the Journal of Materials Processing Technology: Tan, E. Z. E., Pang, J. H. L., & Kaminski, J. (2021). Directed energy deposition build process control effects on microstructure and tensile failure behaviour. In Journal of Materials Processing Technology, 294, 117139, and was presented at the 3rd International Conference on Progress in Additive Manufacturing 2018: Chapter 4 is published as Tan, E. Z. E., Pang, J. H. L., & Kaminski, J. (2018). Laser metal deposition in-situ process control for different build strategies. In 3rd International Conference on Progress in Additive Manufacturing (Pro-AM 2018), 291-296 A study on the fabrication of novel interfacial joint designs for select design parameters was conducted. Two levels for three design parameters: Step angle, step height, and feature geometry were selected to understand their effects on the build quality. Unique forms of defects were found based on the interfacial design parameter combination. By setting an optimisation goal of lowest degree of large defects formed, the most effective combination of interfacial joint design would be to lower the Step Height and Step Angle. On top of this, tighter tolerances can be made for the step joint features in order to ensure that more precise initiation point can be made for the LMD process that produces a more consistent process and a higher quality build. The study investigates two key process variables: step angle and feature geometry, were used to fabricate Stainless Steel AISI 316L specimens. Charpy impact samples were extracted from these specimens such that the notch is located at the interfacial joint. An instrumented Charpy impact test was done to evaluate the impact strength of the interfacial joint designs. The Charpy impact test results show that the V-shaped and stepped interfacial joint designs produce a significant improvement in the mechanical properties of the interfacial joints. This and the previous mentioned study are published as an international patent: “Method of fabricating an interfacial structure and a fabricated interfacial structure” with WO2020167249A1 designation. A numerical study using finite element modelling was done using ABAQUS software to simulate the Charpy impact testing of specimens designed to improve the interfacial strength between a substrate and an LMD built part. Parametric input for material properties was taken from the tensile test studies, interfacial designs were taken from the previous study with variation in step angle and feature geometry. The results for the FEM show a similar trend of impact strength per interfacial joint design to the instrumented empirical Charpy test results, providing a tool for future prediction models for future work other forms of interfacial designs.